The Influence of Career Development and Employee Retention on Work Productivity at PT Swadharma Sarana Informatika Medan - Khairani, Fitri; Indah Lestari Nasution, Annio; Atika (LPPM Universitas Jambi, 2026)
This paper investigates how human resource management strategically functions to elevate corporate productivity within the service sector, specifically by analyzing the impact exerted by career advancement programs and retention schemes on workforce output at PT Swadharma Sarana Informatika (SSI) Medan. Addressing prior empirical discrepancies concerning labor productivity, the present investigation contributes novelty through the amalgamation of these dual dimensions into a unified analytical paradigm. Utilizing a quantitative causal-associative framework, the research derived its participant quota via the Slovin formula, employing SPSS software to execute multiple linear regression and hypothesis validation. Empirical outcomes demonstrate that career development exerts a favorable and statistically meaningful influence on productivity levels, with employee retention manifesting as the paramount determinant governing work output. Furthermore, both independent factors collectively explain 43.8% of the variability observed in employee productivity within the organization. Despite structural limitations confined to a single corporate entity, these insights yield critical managerial directives, emphasizing that harmonizing professional growth pathways with resilient retention frameworks remains vital for maintaining optimal work performance.